Durable conductive silk fabric and preparation method thereof

CN119640582AActive Publication Date: 2025-03-18NANTONG LOVER APPL +1

Patent Information

Application Number
CN202411884872.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-19
Publication Date
2025-03-18
Estimated Expiration
2044-12-19

AI Technical Summary

Technical Problem

In the prior art, the washing resistance of conductive electronic textiles is poor, resulting in insufficient bonding fastness between the conductive material and the textile substrate, affecting flexibility and feel.

Method used

The silk fabric is treated with formic acid to increase the surfactant site, followed by impregnation of silk in a polyphenol solution, then the silver nanowires are synthesized by caffeic acid as a reducing agent, and dispersed in a polyethyleneimine solution, and finally the modified silk fabric is repeatedly impregnated and cured to improve the adhesion of the silver nanowires.

Benefits of technology

It significantly improves the wash resistance and conductivity of conductive silk fabrics, while retaining the flexibility and biocompatibility of silk, and is suitable for flexible sensors and human motion monitoring.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119640582A_ABST
    Figure CN119640582A_ABST
Patent Text Reader

Abstract

The invention discloses a durable conductive silk fabric preparation method, which comprises: pretreating a silk fabric by using a formic acid aqueous solution to obtain a pretreated silk fabric; preparing a polyphenol substance solution, and soaking the pretreated silk in the polyphenol substance solution for treatment to obtain a polyphenol modified silk fabric; the preparation method comprises the following steps: respectively preparing a silver nitrate aqueous solution, a caffeic acid aqueous solution and a polyvinylpyrrolidone aqueous solution, uniformly mixing the three solutions, stirring and reacting at room temperature for 5-10 minutes, heating to 28-30 DEG C, standing and reacting for 3-5 hours, and filtering to obtain a silver nanowire; preparing a polyethyleneimine aqueous solution, and dispersing the silver nanowires in the polyethyleneimine aqueous solution to obtain a silver nanowire / polyethyleneimine dispersion liquid; dipping the polyphenol modified silk fabric in the silver nanowire / polyethyleneimine dispersion liquid for treatment, and repeating dipping and curing to obtain the silver nanowire / polyphenol / polyethyleneimine durable conductive silk fabric.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of functional finishing of textiles, and specifically relates to a method for preparing a durable conductive silk fabric and the durable conductive silk fabric prepared by the preparation method. Background Art

[0002] In recent years, flexible wearable devices have shown broad application prospects in the fields of personal sports monitoring, health care, and intelligent robots. Conductive electronic textiles are the most popular type of flexible wearable devices. Compared with rigid wearable devices, electronic textiles are soft, comfortable, and breathable, have a strong fit with the human body, are light and easy to carry, and are more friendly to the human body than other flexible wearable devices. Conductive fibers / fabrics are necessary components in the preparation of electronic textiles. Usually, carbon-based materials (carbon nanotubes, graphene), metal conductive materials (gold, silver, copper) or conductive polymer materials (polythiophene, polypyrrole, polyaniline), or the new two-dimensional material Mxene in recent years are modified to the surface of textile materials or blended with spinning liquid to prepare conductive fibers / fabrics. Among them, metal conductive materials have the best conductivity compared to other types, and silver nanomaterials are one of the most studied types.

[0003] Silk is a natural animal fiber that is soft, strong, shiny, light, breathable, biodegradable, and biocompatible. With the development of science and technology, people have a deeper understanding of the structure and application of silk. Silk materials have gradually stepped out of the traditional textile field and have shown excellent potential application value in many fields such as biomedicine and flexible electronic devices.

[0004] Compared with conductive polymers and carbon materials, nanosilver has the advantages of light weight, high conductivity and antibacterial effect, and is widely used in electronic skin, biological monitoring, human-computer interaction, environmental monitoring and other fields. For example, nanosilver is deposited on silk fabric by in-situ reduction method of silver ammonia solution to obtain nanosilver / silk fabric with long-lasting antibacterial properties (Journal of Textile Research, 2013, 34(8):5). Compared with nanosilver particles, silver nanowires have a high aspect ratio and better conductivity. For example, Chinese invention patent CN202010518803.1 obtained polyaniline / silver nanowire cotton fiber flexible capacitor electrode material by impregnation method.

[0005] The traditional impregnation method for preparing electronic textiles has the advantage of simple operation, but the biggest problem currently is that the composite electronic textiles obtained by impregnation have poor washing stability. This is mainly because simple impregnation cannot improve the bonding strength between the conductive material and the textile substrate. To solve this problem, the introduction of adhesives is particularly important, but it is a challenge to ensure the flexibility and feel of the textile while improving the bonding strength.

[0006] For example, Chinese invention patent CN201811280979.7 uses polydopamine and polyethyleneimine to modify the surface of the base material to obtain a modified base material, then in situ grows metal organic framework nanofibers on the surface of the modified base material, and undergoes high-temperature carbonization treatment to obtain a highly conductive sensor material, but it needs to undergo high-temperature carbonization treatment at 800°C to 1200°C. Chinese invention patent CN202110038779.6 also carbonizes silk fabrics to obtain conductive fibers, turning the original fibers into carbon fibers, which loses some of the superior properties of the original fibers.

[0007] For example, in Chinese invention patent CN202211114531.4, polyphenol / polyethyleneimine polymer is used as a bonding layer on a textile substrate, and then a metal coating is prepared on the bonding layer by chemical plating to obtain conductive fibers, thereby improving the bonding between the fibers and metal particles. However, the formation of the coating and the metal layer will affect the flexibility of the fibers or fabrics. The chemical plating formula contains more chemical substances, which may affect the performance of silk fibers.

[0008] Another example is the Chinese invention patent CN202210553501.7, which prepared silver nanowires for conductive finishing of cotton fabrics, and obtained cotton fabrics with lower resistance. Due to the naturally twisted structure of cotton fibers, which have large pores, silver nanowires are easy to finish, but even so, the wash fastness is not very high. For silk fabrics, due to the smooth surface of silk and the lack of sufficient anchor points and pores, the wash fastness after conductive finishing is even more difficult to guarantee.

[0009] The disclosure of the above background technology content is only used to assist in understanding the inventive concept and technical solution of the present invention. It does not necessarily belong to the prior art of this patent application. In the absence of clear evidence that the above content has been disclosed before the filing date of this patent application, the above background technology should not be used to evaluate the novelty and creativity of the present application. Summary of the invention

[0010] In view of this, in order to overcome the defects of the prior art, the object of the present invention is to provide a method for preparing a durable conductive silk fabric based on polyethyleneimine.

[0011] In order to achieve the above object, the present invention adopts the following technical solutions:

[0012] A method for preparing a durable conductive silk fabric comprises the following steps:

[0013] S1 pre-treating the silk fabric with a formic acid aqueous solution, washing the treated silk fabric with a sodium carbonate aqueous solution until it becomes neutral, then washing with clean water and drying to obtain a pre-treated silk fabric;

[0014] S2: preparing a polyphenol solution, and immersing the pretreated silk in the polyphenol solution to obtain a polyphenol-modified silk fabric;

[0015] S3 preparation of silver nanowires: respectively preparing a silver nitrate aqueous solution, a caffeic acid aqueous solution and a polyvinyl pyrrolidone aqueous solution, mixing the three solutions evenly, stirring and reacting at room temperature for 5 to 10 minutes, then heating to 28 to 30° C. and allowing to react for 3 to 5 hours, and then filtering to obtain silver nanowires;

[0016] S4 prepares a polyethyleneimine aqueous solution, and disperses the silver nanowires obtained in S3 in the polyethyleneimine aqueous solution to obtain a silver nanowire / polyethyleneimine dispersion;

[0017] S5: The polyphenol-modified silk fabric obtained in S2 is immersed in a silver nanowire / polyethyleneimine dispersion for treatment, and the immersion and curing are repeated to obtain a silver nanowire / polyphenol / polyethyleneimine durable conductive silk fabric.

[0018] According to some preferred implementation aspects of the present invention, the volume fraction of the formic acid aqueous solution in S1 is 20% to 40%, and the pretreatment in S1 comprises the following steps: treating the silk fabric with the formic acid aqueous solution at 15 to 55° C. for 1 to 2 minutes.

[0019] According to some preferred embodiments of the present invention, the mass percentage concentration of the sodium carbonate aqueous solution in S1 is 0.1% to 1%, the drying temperature is 45 to 65° C., and the drying time is 50 to 70 min.

[0020] According to some preferred implementation aspects of the present invention, the polyphenolic substance in S2 is tannic acid and / or dopamine. The polyphenolic substance solution is formed by dissolving the polyphenolic substance in Tris hydrochloric acid buffer, and the concentration of the polyphenolic substance solution is 0.1-10 g / L.

[0021] According to some preferred embodiments of the present invention, the treatment temperature in S2 is 25-45° C. and the treatment time is 1-24 h.

[0022] According to some preferred embodiments of the present invention, the concentration of the silver nitrate aqueous solution configured in S3 is 0.5-3 mol / L, the concentration of the caffeic acid aqueous solution is 2-3 g / L, the concentration of the polyvinyl pyrrolidone aqueous solution is 0.01-0.05 g / L, and the molecular weight of the polyvinyl pyrrolidone is 20,000-200,000 Daltons.

[0023] According to some preferred embodiments of the present invention, the molecular weight of the polyethyleneimine in S4 is 500-5000 Daltons, the concentration of the polyethyleneimine solution is 0.5-10 g / L; the concentration of the silver nanowires in the silver nanowire / polyethyleneimine dispersion is 8-12 mg / mL.

[0024] According to some preferred implementation aspects of the present invention, in the treatment of S5, the temperature of each immersion is 20-30° C., the time is 30-120 min, and the number of immersions is 2-5 times.

[0025] According to some preferred embodiments of the present invention, the curing temperature in S5 is 120-140° C., and the curing time is 5-15 min.

[0026] The present invention also provides a durable conductive silk fabric prepared by any one of the preparation methods described above and its application in flexible devices such as flexible sensors.

[0027] The principle of the present invention is that the surface of the degummed silk fiber is smooth, and even if it is woven into a fabric, the pores inside the fabric are relatively small, and it is difficult to directly arrange the conductive particles or conductive fibers. In order to improve the reaction performance of the silk fabric, the present invention first uses formic acid to treat the silk fabric so that more active sites can be formed on the surface of the silk fabric. Then, by immersing the silk in a polyphenol solution, the active sites are reacted with the polyphenol compounds to further increase the active sites. Afterwards, the present invention adopts a polyvinyl pyrrolidone template method and uses caffeic acid as a reducing agent to synthesize silver nanowires with good conductivity instead of nanoparticles. The conductivity of the silver nanowire is much higher than that of the silver nanoparticles. Since caffeic acid is used as a reducing agent, the surface of the synthesized silver nanowire contains more caffeic acid, which has groups that further react with the active sites on the surface of the silk fiber. At the same time, in order to improve the reaction of caffeic acid with polyphenols, the present invention also adds polyethyleneimine as a cross-linking agent to promote the silver nanowire to be truly covalently grafted to the surface of the silk, construct a conductive structure, and improve the washing fastness. Because silk is relatively smooth, only one dipping and curing will result in a small amount of liquid and insufficient conductivity. Therefore, multiple dipping and then drying and curing are required to improve the adhesion of silver nanowires to the silk surface.

[0028] Due to the adoption of the above technical scheme, the present invention has the following advantages compared with the prior art: the method for preparing the durable conductive silk fabric of the present invention, the durable conductive silk fabric prepared has good conductivity and excellent washability; the flexibility and biocompatibility of silk are retained, and it can be used for the detection of human body movement. And with the repetition of the action, the change of current is also repeatable as a whole. Of course, it can also be fixed on a series of other body parts such as the elbow, wrist, knee, ankle, etc. of the human body, and can be used as a flexible sensor for monitoring human body movement. In addition, the silver nanowire / polyphenol / polyethyleneimine modified silk fabric obtained by the present invention also has antibacterial properties, which can prevent bacterial contamination during the application of the sensor. BRIEF DESCRIPTION OF THE DRAWINGS

[0029] In order to more clearly illustrate the technical solutions in the embodiments of the present invention, the following briefly introduces the drawings required for use in the description of the embodiments. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without creative work.

[0030] Figure 1 This is a photo of the silver nanowire / tannic acid / polyethyleneimine modified silk fabric prepared in Example 2 being connected to a circuit to make a small light bulb glow;

[0031] Figure 2 The antibacterial effect diagram of the silver nanowire / tannic acid / polyethyleneimine modified silk prepared in Example 3: (a) is Staphylococcus aureus cultured in a silk solution without silver nanowire / tannic acid / polyethyleneimine modified silk; (b) is Staphylococcus aureus cultured in a silk solution with silver nanowire / tannic acid / polyethyleneimine modified silk; (c) is Escherichia coli cultured in a silk solution without silver nanowire / tannic acid / polyethyleneimine modified silk; (d) is Escherichia coli cultured in a silk solution with silver nanowire / tannic acid / polyethyleneimine modified silk;

[0032] Figure 3 This is a performance test diagram of the silver nanowire / dopamine / polyethyleneimine modified silk fabric prepared in Example 6 for finger motion sensing. DETAILED DESCRIPTION

[0033] In order to enable those skilled in the art to better understand the technical solution of the present invention, the technical solution in the embodiments of the present invention will be clearly and completely described below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work should fall within the scope of protection of the present invention.

[0034] The method for preparing the durable conductive silk fabric of the present invention comprises the following steps:

[0035] (1) pre-treating a silk fabric with a formic acid aqueous solution, washing the treated silk fabric with a sodium carbonate aqueous solution until it becomes neutral, then washing with clean water and drying to obtain a pre-treated silk fabric;

[0036] The specific steps are as follows: the silk fabric is treated with a 20% to 40% formic acid aqueous solution at 15 to 55°C for 1 to 2 minutes, the treated silk fabric is first washed with a low-concentration sodium carbonate solution with a mass percentage concentration of 0.1% to 1% to neutral, and then washed with clean water and dried to obtain pretreated silk. This step can roughen the surface of the silk fabric and provide more reaction sites. The drying temperature is 45 to 65°C and the drying time is 50 to 70 minutes.

[0037] (2) preparing a polyphenol solution, and immersing the pretreated silk in the polyphenol solution for treatment to obtain a polyphenol-modified silk fabric;

[0038] The polyphenol solution is formed by dissolving the polyphenol in Tris hydrochloric acid buffer, the concentration of the polyphenol solution is 0.1-10 g / L, the treatment temperature is 25-45° C., the treatment time is 1-24 hours, and the polyphenol is tannic acid and / or dopamine.

[0039] (3) Preparation of silver nanowires

[0040] A silver nitrate aqueous solution with a concentration of 0.5 to 3 mol / L, a caffeic acid aqueous solution with a concentration of 2 to 3 g / L, and a polyvinyl pyrrolidone aqueous solution with a concentration of 0.01 to 0.05 g / L are respectively prepared, the three solutions are mixed evenly, stirred at room temperature for 5 to 10 minutes, then heated to 28 to 30°C and allowed to stand for 3 to 5 hours, and then filtered to obtain silver nanowires. The molecular weight of the polyvinyl pyrrolidone is 20,000 to 200,000 Daltons.

[0041] (4) Preparing a 0.5-10 g / L polyethyleneimine aqueous solution, dispersing the silver nanowires obtained above in the polyethyleneimine aqueous solution to obtain a silver nanowire / polyethyleneimine dispersion.

[0042] The molecular weight of polyethyleneimine is 500-5000 Daltons, and the concentration of silver nanowires in the prepared silver nanowire / polyethyleneimine dispersion is 8-12 mg / mL.

[0043] (5) The polyphenol-modified silk fabric obtained above is immersed in a silver nanowire / polyethyleneimine dispersion for treatment, and the immersion and curing are repeated to obtain a silver nanowire / polyphenol / polyethyleneimine durable conductive silk fabric.

[0044] The temperature of each immersion is 20-30°C, the time is 30-120 minutes, the curing temperature is 120-140°C, and the curing time is 5-15 minutes.

[0045] Polyethyleneimine is an industrial polymer raw material with a high degree of main chain branching and a large number of reactive groups (amine groups). It is widely used in papermaking, catalysis, flocculants, dye fixatives, fiber modification, printing and dyeing auxiliaries, ion exchange resins and other fields, and has certain environmental friendliness.

[0046] Tannic acid is a natural substance found in plants. It is green and environmentally friendly, with a wide range of sources and no pollution. It also has good biocompatibility and is basically harmless to the human body. It has multiple functional groups, biocompatibility, and good adhesion. Therefore, it is more appropriate to introduce tannic acid on silk textiles. In order to further improve the adhesion stability of tannic acid, polyethyleneimine can be introduced into the reaction system. Polyethyleneimine and tannic acid are compounded, and the two can further improve the conductive stability through the attraction of positive and negative charges. At the same time, it can also improve the positive charge, which is conducive to the subsequent introduction of negatively charged silver nanowire networks.

[0047] Dopamine is a type of biomimetic adhesive that is very similar to the mucus protein component in mussel foot silk protein. Dopamine has abundant functional groups such as catechol and amino groups in its molecular structure, which gives it universal adhesion and is relatively safe and environmentally friendly. Therefore, it can be used in the preparation of functional textiles by the dipping method. However, the non-covalent forces between dopamine or between polydopamine after oxidative self-polymerization are still weak and are still easy to fall off at the interface. For this reason, polyethyleneimine can be introduced and compounded with it to increase the cross-linking between dopamine molecules. Dopamine and polyethyleneimine can undergo Shiff base or Michael addition reaction to form a stable cross-linked network. Therefore, dopamine / polyethyleneimine can be modified to the surface of silk as an adhesion layer to prepare durable conductive silk fabrics.

[0048] Example 1

[0049] The method for preparing the durable conductive silk fabric based on tannic acid in this embodiment specifically comprises the following steps:

[0050] (1) Degummed silk was treated with 20% formic acid at 35°C for 2 minutes. The treated silk was first washed with a 0.5% low concentration sodium carbonate solution until it was neutral, then washed with clean water and dried to obtain a pretreated silk fabric. This step can roughen the surface of the silk fabric and provide more reaction sites. The drying temperature is 55°C and the drying time is 60 minutes.

[0051] (2) The pretreated silk fabric was immersed in 0.2 g / L tannic acid solution (tris hydrochloric acid buffer solution as solvent) at a reaction temperature of 40° C. for 3 h to obtain tannic acid-modified silk fabric.

[0052] (3) Prepare 1 mol / L silver nitrate aqueous solution, 2 g / L caffeic acid aqueous solution and 0.02 g / L polyvinyl pyrrolidone aqueous solution respectively, mix the three solutions evenly, stir and react at room temperature for 8 minutes, then heat to 29°C and let stand for 4 hours, then filter to obtain silver nanowires. The molecular weight of polyvinyl pyrrolidone is 50,000 Daltons.

[0053] (4) preparing a 0.7 g / L polyethyleneimine aqueous solution, dispersing the silver nanowires in the polyethyleneimine aqueous solution, and obtaining a silver nanowire / polyethyleneimine dispersion, wherein the molecular weight of the polyethyleneimine is 1000 Daltons, and the concentration of the silver nanowires in the prepared silver nanowire / polyethyleneimine dispersion is 10 mg / mL.

[0054] (5) The tannic acid-modified silk fabric was immersed in the silver nanowire / polyethyleneimine dispersion at 25° C. for 90 min, and then cured at 130° C. for 10 min. The immersion and curing were repeated three times to obtain a silver nanowire / tannic acid / polyethyleneimine-modified silk fabric.

[0055] The square resistance value of Example 1 was measured once after each curing, and the results are shown in Table 1. After the square resistance value of the conductive silk fabric obtained after three curings was measured, it was washed 50 times (standard soap washing cycle 10 times) according to the AATCC 61-2006 washing fastness test standard, and its square resistance was continued to be measured. The results are shown in Table 2.

[0056] Example 2

[0057] The method for preparing the durable conductive silk fabric based on tannic acid in this embodiment specifically comprises the following steps:

[0058] (1) Treat the silk with 30% formic acid at 20°C for 2 minutes. The treated silk is first washed with a 0.2% sodium carbonate solution until it becomes neutral, then washed with clean water and dried to obtain a pretreated silk fabric. This step can roughen the surface of the silk fabric and provide more reaction sites. The drying temperature is 60°C and the drying time is 50 minutes.

[0059] (2) The pretreated silk fabric was immersed in a 0.5 g / L tannic acid solution (using tris hydrochloric acid buffer as solvent) at a reaction temperature of 35° C. for a reaction time of 6 h to obtain a tannic acid-modified silk fabric.

[0060] (3) 0.9 mol / L silver nitrate aqueous solution, 2.2 g / L caffeic acid aqueous solution and 0.03 g / L polyvinyl pyrrolidone aqueous solution were prepared respectively, the three solutions were mixed evenly, stirred for reaction at room temperature for 10 min, then heated to 30° C. and allowed to react for 3 h, and then filtered to obtain silver nanowires. The molecular weight of polyvinyl pyrrolidone was 40,000 Daltons.

[0061] (4) preparing a 1 g / L polyethyleneimine aqueous solution, dispersing the silver nanowires in the polyethyleneimine aqueous solution, and obtaining a silver nanowire / polyethyleneimine dispersion, wherein the molecular weight of the polyethyleneimine is 600 Daltons, and the concentration of the silver nanowires in the prepared silver nanowire / polyethyleneimine dispersion is 11 mg / mL.

[0062] (5) The polyphenol-modified silk fabric was immersed in the silver nanowire / polyethyleneimine dispersion at 30° C. for 30 min, and then cured at 120° C. for 15 min. The immersion and curing were repeated three times to obtain a silver nanowire / tannic acid / polyethyleneimine-modified silk fabric.

[0063] Figure 1 This is a photo of the silver nanowire / tannic acid / polyethyleneimine modified silk prepared in Example 2 being connected to a circuit to make a small light bulb glow. This indicates that the silver nanowire / tannic acid / polyethyleneimine modified silk fabric has excellent conductivity and can be connected to a circuit as a flexible electronic component.

[0064] Example 3

[0065] The method for preparing the durable conductive silk fabric based on tannic acid in this embodiment specifically comprises the following steps:

[0066] (1) Treat the silk with 40% formic acid at 25°C for 1 minute. The treated silk is first washed with a 0.7% sodium carbonate solution until it becomes neutral, then washed with clean water and dried to obtain a pretreated silk fabric. This step can roughen the surface of the silk fabric and provide more reaction sites. The drying temperature is 45°C and the drying time is 70 minutes.

[0067] (2) The pretreated silk fabric was immersed in a 1 g / L tannic acid solution (using tris hydrochloric acid buffer as solvent) at a reaction temperature of 30° C. for 8 h to obtain a tannic acid-modified silk fabric.

[0068] (3) Prepare 2 mol / L silver nitrate aqueous solution, 2.8 g / L caffeic acid aqueous solution and 0.05 g / L polyvinyl pyrrolidone aqueous solution respectively, mix the three solutions evenly, stir and react at room temperature for 8 min, then heat to 28° C. and let stand for 5 h, then filter to obtain silver nanowires. The molecular weight of polyvinyl pyrrolidone is 100,000 Daltons.

[0069] (4) preparing a 0.5 g / L polyethyleneimine aqueous solution, dispersing the silver nanowires in the polyethyleneimine aqueous solution, and obtaining a silver nanowire / polyethyleneimine dispersion, wherein the molecular weight of the polyethyleneimine is 4000 Daltons, and the concentration of the silver nanowires in the prepared silver nanowire / polyethyleneimine dispersion is 12 mg / mL.

[0070] (5) The tannic acid-modified silk fabric was immersed in a 12 mg / mL silver nanowire / polyethyleneimine dispersion at 20° C. for 120 min, and then cured at 140° C. for 5 min. The immersion and curing were repeated 5 times to obtain a silver nanowire / tannic acid / polyethyleneimine-modified silk fabric.

[0071] Example 4

[0072] The method for preparing the durable conductive silk fabric based on dopamine in this embodiment specifically comprises the following steps:

[0073] (1) Treat the silk with 20% formic acid at 35°C for 2 minutes. The treated silk is first washed with a 0.3% low-concentration sodium carbonate solution until it becomes neutral, then washed with clean water and dried to obtain a pretreated silk fabric. This step can roughen the surface of the silk fabric and provide more reaction sites. The drying temperature is 55°C and the drying time is 60 minutes.

[0074] (2) The silk fabric was immersed in a 5 g / L dopamine solution (using tris hydrochloric acid buffer as solvent) at a reaction temperature of 40° C. for a reaction time of 3 h to obtain a dopamine-modified silk fabric.

[0075] (3) Preparation of silver nanowires: 2.5 mol / L silver nitrate aqueous solution, 2.8 g / L caffeic acid aqueous solution and 0.04 g / L polyvinyl pyrrolidone aqueous solution were prepared respectively, the three solutions were mixed evenly, stirred at room temperature for 6 min, then heated to 28°C and allowed to react for 5 h, and then filtered to obtain silver nanowires. The molecular weight of polyvinyl pyrrolidone was 30,000 Daltons.

[0076] (4) preparing an 8 g / L polyethyleneimine aqueous solution, dispersing the silver nanowires obtained above in the polyethyleneimine aqueous solution to obtain a silver nanowire / polyethyleneimine dispersion, wherein the molecular weight of the polyethyleneimine is 1000 Daltons, and the concentration of the silver nanowires in the prepared silver nanowire / polyethyleneimine dispersion is 9 mg / mL.

[0077] (5) The dopamine-modified silk fabric was immersed in a 9 mg / mL silver nanowire / polyethyleneimine dispersion at 25° C. for 90 min, and then cured at 130° C. for 15 min. The immersion and curing were repeated three times to obtain a silver nanowire / dopamine / polyethyleneimine-modified silk fabric.

[0078] The square resistance value was measured after each curing, and the results are shown in Table 1. After the square resistance value of the conductive silk fabric obtained after three curings was measured, it was washed 50 times (10 standard soap washing cycles) according to the AATCC 61-2006 washing fastness test standard, and its square resistance was further measured. The results are shown in Table 2.

[0079] Example 5

[0080] The method for preparing the durable conductive silk fabric based on dopamine in this embodiment specifically comprises the following steps:

[0081] (1) Degummed silk was treated with 30% formic acid at 20°C for 2 minutes. The treated silk was first washed with a 0.5% sodium carbonate solution until it was neutral, then washed with clean water and dried to obtain a pretreated silk fabric. This step can roughen the surface of the silk fabric and provide more reaction sites. The drying temperature was 60°C and the drying time was 50 minutes.

[0082] (2) The silk fabric is immersed in a 3 g / L dopamine solution (using tris hydrochloric acid buffer as solvent), the reaction temperature is 45° C., and the reaction time is 2 h; and the dopamine-modified silk fabric is obtained.

[0083] (3) Preparation of silver nanowires: 1.8 mol / L silver nitrate aqueous solution, 2.4 g / L caffeic acid aqueous solution and 0.03 g / L polyvinyl pyrrolidone aqueous solution were prepared respectively, the three solutions were mixed evenly, stirred for reaction at room temperature for 8 min, then heated to 30° C. and allowed to react for 3 h, and then filtered to obtain silver nanowires. The molecular weight of polyvinyl pyrrolidone was 100,000 Daltons.

[0084] (4) preparing a 5 g / L polyethyleneimine aqueous solution, dispersing the silver nanowires obtained above in the polyethyleneimine aqueous solution to obtain a silver nanowire / polyethyleneimine dispersion, wherein the molecular weight of the polyethyleneimine is 800 Daltons, and the concentration of the silver nanowires in the prepared silver nanowire / polyethyleneimine dispersion is 10 mg / mL.

[0085] (5) The dopamine-modified silk fabric was immersed in a 10 mg / mL silver nanowire / polyethyleneimine dispersion at 30° C. for 30 min, and then cured at 120° C. for 15 min. The immersion and curing were repeated twice to obtain a silver nanowire / dopamine / polyethyleneimine-modified silk fabric.

[0086] Example 6

[0087] The method for preparing the durable conductive silk fabric based on dopamine in this embodiment specifically comprises the following steps:

[0088] (1) The degummed silk was treated with 40% formic acid at 25°C for 1 min. The treated silk was first washed with a 0.6% low concentration sodium carbonate solution until it became neutral, then washed with clean water and dried to obtain a pretreated silk fabric. This step can roughen the surface of the silk fabric and provide more reaction sites. The drying temperature is 45°C and the drying time is 70 min.

[0089] (2) The silk fabric is immersed in a 1 g / L dopamine solution (using tris hydrochloric acid buffer as solvent) at a reaction temperature of 30° C. for a reaction time of 1 h to obtain a dopamine-modified silk fabric.

[0090] (3) Preparation of silver nanowires: 2.8 mol / L silver nitrate aqueous solution, 2.7 g / L caffeic acid aqueous solution and 0.04 g / L polyvinyl pyrrolidone aqueous solution were prepared respectively, the three solutions were mixed evenly, stirred for reaction at room temperature for 10 min, then heated to 30° C. and allowed to react for 3.5 h, and then filtered to obtain silver nanowires. The molecular weight of polyvinyl pyrrolidone was 100,000 Daltons.

[0091] (4) preparing a 12 g / L polyethyleneimine aqueous solution, dispersing the silver nanowires obtained above in the polyethyleneimine aqueous solution to obtain a silver nanowire / polyethyleneimine dispersion, wherein the molecular weight of the polyethyleneimine is 3000 Daltons, and the concentration of the silver nanowires in the prepared silver nanowire / polyethyleneimine dispersion is 10 mg / mL.

[0092] (4) The dopamine-modified silk fabric was immersed in 3 mL of a 10 mg / mL silver nanowire / polyethyleneimine dispersion at room temperature (20° C.) for 120 min, and then cured at 140° C. for 15 min. The immersion and curing were repeated 5 times to obtain a silver nanowire / dopamine / polyethyleneimine-modified silk fabric.

[0093] Comparative Example 1

[0094] This comparative example is used to investigate the effect of not adding polyphenol / polyethyleneimine on the durability of conductive silk. The preparation of the silver nanowire-modified silk fabric in this comparative example specifically includes the following steps:

[0095] (1) Degummed silk was treated with 20% formic acid at 35°C for 2 minutes, the treated silk was first washed with a 0.2% sodium carbonate solution until neutral, then washed with clean water and dried to obtain a pretreated silk fabric. The drying temperature was 55°C and the drying time was 60 minutes.

[0096] (2) Preparation of silver nanowires: 2 mol / L silver nitrate aqueous solution, 2 g / L caffeic acid aqueous solution and 0.04 g / L polyvinyl pyrrolidone aqueous solution were prepared respectively, the three solutions were mixed evenly, stirred for reaction at room temperature for 10 min, then heated to 30° C. and allowed to react for 4 h, and then filtered to obtain silver nanowires. The molecular weight of polyvinyl pyrrolidone was 50,000 Daltons.

[0097] (3) The pretreated silk fabric was immersed in a silver nanowire dispersion liquid with a concentration of 10 mg / mL at 25° C. for 90 min, and then cured at 130° C. for 10 min. The immersion and curing were repeated 3 times to obtain a silver nanowire-modified silk fabric. The silver nanowire dispersion liquid is obtained by dispersing silver nanowires in water.

[0098] In step (3) of this comparative example, the square resistance value was measured once after each curing. After the square resistance value of the conductive silk fabric obtained after three curings was measured, it was washed 50 times (10 standard soap washing cycles) according to the AATCC 61-2006 washing fastness test standard, and its square resistance was further measured. The results are shown in Table 2.

[0099] As shown in Table 2, the resistance of the silk treated with silver nanowires only without tannic acid / polyethyleneimine treatment decreased significantly after washing, and soon rose to 2.73×10 5 Ω / sq.

[0100] Comparative Example 2

[0101] This comparative example is used to investigate the importance of adding polyethyleneimine to the durability of silver nanowire / tannic acid modified silk fabric. The preparation of the silver nanowire / tannic acid modified silk fabric in this comparative example specifically includes the following steps:

[0102] (1) Degummed silk was treated with 20% formic acid at 35°C for 2 minutes, the treated silk was first washed with a 0.5% sodium carbonate solution until neutral, then washed with clean water and dried to obtain a pretreated silk fabric. The drying temperature was 55°C and the drying time was 60 minutes.

[0103] (2) The silk fabric is immersed in a 0.2 g / L tannic acid solution (using tris hydrochloric acid buffer as solvent) at a reaction temperature of 40° C. for a reaction time of 3 h to obtain a tannic acid-modified silk fabric.

[0104] (3) Preparation of silver nanowires: 1 mol / L silver nitrate aqueous solution, 2 g / L caffeic acid aqueous solution and 0.02 g / L polyvinyl pyrrolidone aqueous solution were prepared respectively, the three solutions were mixed evenly, stirred for reaction at room temperature for 8 min, then heated to 29° C. and allowed to react for 4 h, and then filtered to obtain silver nanowires. The molecular weight of polyvinyl pyrrolidone was 50,000 Daltons.

[0105] (4) The tannic acid modified silk fabric was immersed in a silver nanowire dispersion liquid with a concentration of 10 mg / mL at room temperature 25° C. for 90 min, and then cured at 130° C. for 10 min. The immersion and curing were repeated 3 times to obtain a silver nanowire / tannic acid modified silk fabric. The silver nanowire dispersion liquid is obtained by dispersing silver nanowires in water.

[0106] After the square resistance value of the conductive silk fabric obtained after three curings was measured, it was washed 50 times (standard soap washing cycle 10 times) according to the AATCC 61-2006 washing fastness test standard, and its square resistance was further measured. The results are shown in Table 2.

[0107] As shown in Table 2, the silk treated with tannic acid and silver nanowires without the introduction of polyethyleneimine has a higher resistance drop after washing than the silk treated with tannic acid / polyethyleneimine. The resistance test results before and after washing of the two comparative examples and Example 1 show that the tannic acid / polyethyleneimine treatment greatly improves the durability of the silver nanowire conductive silk fabric.

[0108] Comparative Example 3

[0109] This comparative example is used to investigate the importance of adding polyethyleneimine to the durability of silver nanowire / dopamine modified silk fabric. The preparation of the silver nanowire / dopamine modified silk fabric in this comparative example specifically includes the following steps:

[0110] (1) Treat the silk with 20% formic acid at 35°C for 2 minutes. The treated silk is first washed with a 0.3% sodium carbonate solution until it becomes neutral, then washed with clean water and dried to obtain a pretreated silk fabric. This step can roughen the surface of the silk fabric and provide more reaction sites. The drying temperature is 55°C and the drying time is 60 minutes.

[0111] (2) The silk fabric was immersed in a 5 g / L dopamine solution (using tris hydrochloric acid buffer as solvent) at a reaction temperature of 40° C. for a reaction time of 3 h to obtain a dopamine-modified silk fabric.

[0112] (3) Preparation of silver nanowires: 2.5 mol / L silver nitrate aqueous solution, 2.8 g / L caffeic acid aqueous solution and 0.04 g / L polyvinyl pyrrolidone aqueous solution were prepared respectively, the three solutions were mixed evenly, stirred for reaction at room temperature for 6 min, then heated to 28°C and allowed to react for 5 h, and then filtered to obtain silver nanowires. The molecular weight of polyvinyl pyrrolidone was 50,000 Daltons.

[0113] (4) The dopamine-modified silk fabric was immersed in a silver nanowire dispersion having a concentration of 9 mg / mL at room temperature of 25° C. for 90 min, and then cured at 130° C. for 15 min. The immersion and curing were repeated 3 times to obtain a silver nanowire / dopamine-modified silk fabric. The silver nanowire dispersion was obtained by dispersing silver nanowires in water.

[0114] After the square resistance value of the conductive silk fabric obtained after three curings was measured, it was washed 50 times (standard soap washing cycle 10 times) according to the AATCC 61-2006 washing fastness test standard, and its square resistance was further measured. The results are shown in Table 2. "~" in the table means approximately.

[0115] Table 1 Sheet resistance values ​​of the modified silk fabrics of Example 1 and Example 4 after being immersed in silver nanowire solution for different times and after being soaped for 50 times

[0116]

[0117] As shown in Table 1, silk itself is non-conductive. Through the treatment of the present invention, as the number of times of dipping in the silver nanowire solution increases, the square resistance of the conductive silk fabric obtained decreases significantly. The silver nanowire / tannic acid / polyethyleneimine modified silk fabric prepared in Example 1 shows good conductive stability. After 50 soap washings, the square resistance value only increases to 283.7Ω / sq, showing excellent wash resistance. The silver nanowire / dopamine / polyethyleneimine modified silk fabric obtained in Example 4 also significantly decreases as the number of times of dipping in the silver nanowire solution increases. The final square resistance is about 7.1Ω / sq, and tends to be stable. Under the action of dopamine / polyethyleneimine, the silver nanowire / dopamine / polyethyleneimine modified silk fabric shows good conductive stability. After long-term soap washing, the square resistance value only increases to 13.5Ω / sq.

[0118] Table 2 Comparison of washing durability of conductive silk prepared in Example 1, Example 4 and different comparative examples

[0119]

[0120] According to the results of Comparative Examples 1 and 2 in Table 2, it can be found that the tannic acid / polyethyleneimine adhesion layer gives the conductive silk fabric good conductive stability. The polyethyleneimine component gives the silk fabric surface more positive charge, which makes it easy for the silver nanowires with negative charge on the surface to be deposited on the silk surface more in a short time by electrostatic adsorption, thereby giving the silk surface a denser silver nanowire conductive network. Tannic acid, as a modified intermediate layer, is connected to the silk fabric through strong hydrogen bonding on the one hand, and on the other hand, it gives the silk fabric surface more phenolic hydroxyl groups, which can easily coordinate and complex with the silver nanowire surface, further ensuring the stable deposition of silver nanowires on the fabric surface. In addition, tannic acid and polyethyleneimine attract each other through electrostatic force, which improves the durability of the silver nanowire conductive silk fabric.

[0121] According to the results of Comparative Examples 3 and 4 in Table 2, it can also be found that dopamine / polyethyleneimine also gives conductive silk fabrics good conductive stability. Dopamine / polyethyleneimine gives the surface of silk fabrics more positive charge, which makes it easy for the silver nanowires with negative charge on the surface to be deposited on the silk surface in a short time by electrostatic adsorption, thereby giving the silk surface a denser silver nanowire conductive network. In addition, dopamine / polyethyleneimine gives the surface of silk fabrics more phenolic hydroxyl and amino functional groups, so that it can be complexed with more silver nanowires, and the silver nanowires are stably deposited on the surface of the fabric, which ultimately promotes the preparation of durable silver nanowire conductive silk fabrics.

[0122] Figure 2 The antibacterial effect diagram of the silver nanowire / tannic acid / polyethyleneimine modified silk prepared in Example 3 is shown in FIG. Figure 2 It can be seen that the number of Staphylococcus aureus colonies cultured without adding silver nanowire / tannic acid / polyethyleneimine modified silk solution (a) is about 105, and the number of Staphylococcus aureus colonies cultured with adding silver nanowire / tannic acid / polyethyleneimine modified silk solution (b) is about 8; the number of Escherichia coli colonies cultured without adding silver nanowire / tannic acid / polyethyleneimine modified silk solution (c) is about 92, and the number of Escherichia coli colonies cultured with adding silver nanowire / tannic acid / polyethyleneimine modified silk solution (d) is about 24. The antibacterial rate of silver nanowire / tannic acid / polyethyleneimine modified silk for Staphylococcus aureus can reach 92.38%, and the antibacterial rate for Escherichia coli can reach 73.91%. The above results show that in addition to excellent conductivity, silver nanowire / tannic acid / polyethyleneimine modified silk also has good antibacterial properties, providing an antibacterial solution for demanding wearable designs.

[0123] Figure 3The performance test diagram of the silver nanowire / dopamine / polyethyleneimine modified silk fabric used for the finger motion sensor prepared in Example 6. As mentioned above, the silver nanowire / dopamine / polyethyleneimine modified silk can be connected to the conductive path as a flexible electronic component. When a certain mechanical force is applied to it to deform it, it can convert the mechanical signal into an electrical signal and feed it back. Figure 3 As shown, under the application of a constant voltage, the silver nanowire / dopamine / polyethyleneimine modified silk is attached to the finger joints and can feedback obvious real-time relative resistance changes when the fingers are straightened / bent, indicating that the modified silk fabric prepared by the present invention can be used as a sensor for finger and other limb movements.

[0124] The present invention discloses a durable conductive silk fabric and a preparation method thereof. In order to improve the bonding strength between silver nanowires and silk fabrics and improve the durability and washing stability of the fabrics after finishing, the silk fabrics are treated with formic acid before being impregnated with silver nanowires, and then a tannic acid solution or a dopamine solution is added to modify the silk fabrics; the silver nanowires are prepared by polyphenols, and finally the modified silk fabrics are impregnated with a silver nanowire / polyethyleneimine dispersion to prepare a silver nanowire / polyphenol / polyethyleneimine modified silk fabric. The preparation method of the durable conductive silk fabric of the present invention has a simple process, good conductivity, and excellent antibacterial properties, and has excellent washing resistance compared to other conductive fibers / fabrics prepared by impregnation methods. The prepared silver nanowire conductive silk is antibacterial and has good electrical conductivity, and can be used for flexible sensing. It has good application prospects in flexible wearable fields such as human motion detection, electronic textiles, electrothermal textiles, and health monitoring.

[0125] The above embodiments are only for illustrating the technical concept and features of the present invention, and their purpose is to enable people familiar with this technology to understand the contents of the present invention and implement them accordingly. They cannot be used to limit the protection scope of the present invention. Any equivalent changes or modifications made according to the spirit of the present invention should be included in the protection scope of the present invention.

[0126] The endpoints and any values ​​of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoint values ​​of each range, the endpoint values ​​of each range and the individual point values, and the individual point values ​​can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.

Claims

1. A method for preparing a durable conductive silk fabric, characterized in that: The steps include: The silk fabric is pretreated with a formic acid aqueous solution, the treated silk fabric is first washed with a sodium carbonate aqueous solution until it becomes neutral, then washed with clean water and dried to obtain a pretreated silk fabric; preparing a polyphenol solution, and immersing the pretreated silk in the polyphenol solution for treatment to obtain a polyphenol-modified silk fabric; A silver nitrate aqueous solution, a caffeic acid aqueous solution and a polyvinyl pyrrolidone aqueous solution are respectively prepared, the three solutions are mixed evenly, stirred for reaction at room temperature for 5 to 10 minutes, then heated to 28 to 30° C. and allowed to react for 3 to 5 hours, and filtered to obtain silver nanowires; preparing a polyethyleneimine aqueous solution, dispersing the silver nanowires in the polyethyleneimine aqueous solution, and obtaining a silver nanowire / polyethyleneimine dispersion; The polyphenol-modified silk fabric is immersed in the silver nanowire / polyethyleneimine dispersion for treatment, and the immersion and curing are repeated to obtain a silver nanowire / polyphenol / polyethyleneimine durable conductive silk fabric.

2. The preparation method according to claim 1, characterized in that: The volume fraction of the formic acid aqueous solution is 20% to 40%; the pretreatment comprises the following steps: treating the silk fabric with the formic acid aqueous solution at 15 to 55° C. for 1 to 2 minutes.

3. The preparation method according to claim 1, characterized in that: The mass percentage concentration of the sodium carbonate aqueous solution is 0.1% to 1%; the drying temperature is 45 to 65° C., and the drying time is 50 to 70 minutes.

4. The preparation method according to claim 1, characterized in that: The polyphenolic substance is tannic acid and / or dopamine; the polyphenolic substance solution is formed by dissolving the polyphenolic substance in Tris hydrochloric acid buffer, and the concentration of the polyphenolic substance solution is 0.1-10 g / L.

5. The preparation method according to claim 1, characterized in that: The pretreated silk is immersed in the polyphenol solution for treatment at a temperature of 25 to 45° C. for a time of 1 to 24 hours.

6. The preparation method according to claim 1, characterized in that: The concentration of the silver nitrate aqueous solution is 0.5-3 mol / L, the concentration of the caffeic acid aqueous solution is 2-3 g / L, the concentration of the polyvinyl pyrrolidone aqueous solution is 0.01-0.05 g / L, and the molecular weight of the polyvinyl pyrrolidone is 20000-200000 Dalton.

7. The preparation method according to claim 1, characterized in that: The molecular weight of the polyethyleneimine is 500-5000 Daltons, the concentration of the polyethyleneimine solution is 0.5-10 g / L; the concentration of the silver nanowires in the silver nanowire / polyethyleneimine dispersion is 8-12 mg / mL.

8. The preparation method according to claim 1, characterized in that: When the polyphenol-modified silk fabric is immersed in the silver nanowire / polyethyleneimine dispersion for treatment, the number of immersions is 2 to 5 times, the immersion temperature is 20 to 30° C., and the time of each immersion is 30 to 120 minutes.

9. The preparation method according to claim 1, characterized in that: The curing temperature is 120-140° C. and the curing time is 5-15 minutes each time.

10. A durable conductive silk fabric prepared according to the preparation method according to any one of claims 1 to 9.

Citation Information

Patent Citations

  • Preparation method of nanofiber-based high conductivity gas sensor materials

    CN109400937B

  • Polyaniline / silver nanowire cotton fiber capacitor electrode material and preparation method

    CN111653433B

  • A method for preparing carbon nanotubes based on silk templates

    CN112794309B

  • A method for preparing silver nanowires at room temperature based on small molecule phenolic acids

    CN114985756B

  • Electrically conductive textile element and method of making same

    CN115323790A

Cited By

  • Flexible triboelectric sensor based on modified conductive fabric and preparation method thereof

    CN121916952A